Eksplorasi sistem konstruksi rumah fala di Kabupaten Alor - Lapenangga, Apris Kefas; Jeraman, Pilipus; Lake, Reginaldo Christophori; Talan, John Petrus; Morakinyo, Kolawole Opeyemi; Taiwo, Richard Oluseyi; Oludoyi, Kolawole Olayemi; Daton, Richardus; Mukin, Andreas K. S. (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The fala house is one of the traditional houses of the Abui tribe in Alor which is also known as a warehouse house. This building is ± 16 m high and consists of 4 floors with functions as a residence, barn, and storage area for heirlooms. This building's design and dimensions are also tailored to withstand the frequent high winds and earthquakes in the Alor region. To provide the Alor community as a whole with literature and a reference for creating disaster-resistant dwellings, this study intends to investigate the fala house construction system. An ethnographic design in conjunction with an exploratory description is the methodology employed to examine the Fala House's construction system. One of Takpala Village's thirteen fala homes serves as the research item. Purposive sampling was used to identify the home of the village chief, who served as the resource person, to choose this item. While secondary data was gathered through a review of the literature, primary data was acquired through close inspection and recording of the artifacts as well as technical information on workmanship and local names of fala house construction through interviews. According to research, the Fala house is built using a traditional method in which the main pillar is buried directly in the ground. The attic pillars that rest on the main beam are braced and connected to the building using a tie system. Because fala houses are built with a building method that can withstand shocks from earthquakes and severe winds, they have withstood a lengthy time of disaster adaptation and are still standing today.